“Diya”-Related Burn Injuries during the Diwali Period: A 5-Year Retrospective Review from a Tertiary Care Hospital in India - Gupta, Deepti; Chand, Nemi; Nanavati, Nupoor; Chauhan, Aakash; Sarabahi, Sujata (Indian Journal of Plastic Surgery, 2024)
Background Diwali is a festival that is passionately celebrated by Indians all across the globe. Fire hazards associated with this festival are well known. Our hospital is a tertiary care burn center and caters to a patient population from all over North India. Firecracker burns and diya burns constitute two major causes of burn injuries during the festival of Diwali. Since, diya-related burn injuries have been overlooked in the past, this study was primarily designed to study the demographical data of “diya burns” during Diwali.Materials and Methods The departmental records were analyzed for 3 days around Diwali festival over a period of 5 years from 2018 to 2022.Results The results indicated that almost a third of all Diwali-related burns were caused by diyas (32.5%). A “burning diya left on floor” was the main reason for these injuries. Females were the most affected (70.4%). Additionally, one-third of these patients required admission.Conclusion This study emphasizes the need for raising awareness regarding the proper use of “diyas” to bring down the incidence of such preventable burn injuries.
Keywords: thermal burns; Diwali; diya; earthen lamp